EKSPLORASI MATEMATIKA PADA TOMBI-TOMBI MANDAR SEBAGAI SUMBER BELAJAR DALAM PERSPEKTIF ETNOMATEMATIKA - Asiah, Nur; Kusumayanti, Andi; Suharti, Suharti; Asmar, Andi Ariq Fakhri (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2025)
This research aims for explore draft mathematics in Tombi-Tombi Mandar, accessories traditional from the Mandar Tribe, as source study in perspective ethnomathematics. This study uses approach qualitative with method ethnography for understand integration culture local in learning mathematics. Data collected through interviews, observations, and documentation at the Mandar Museum, Majene, west Sulawesi. The results of the study show that various type Tombi-Tombi Mandar, such as Tombi A'di-A'di , Tombi Ana'i, Tombi Cucur, Tombi Bu'ang, and Tombi Jijir, contain draft geometry and patterns numbers. The concept of square, rectangle, semicircle, circle, triangle, and parallelogram, and repeating patterns. This finding confirms importance integration culture in learning mathematics for increase understanding student at a time to preserve cultural heritage. By utilizing Tombi-Tombi Mandar as source learning, expected learning mathematics become more contextual, interesting, and meaningful.